Ensuring Equitable and Inclusive School Education: Analytical Review of Primary Stakeholders - Doungel, C Thangminlal (THE PRIMARY TEACHER, 2022)
Education is the single greatest tool to achieve social justice and equality in society (NEP, 2020, p. 23). School education being a primordial tool at the forefront in this regard, plays a critical role. It is worth noting that in the context of India, efforts to ensure equitable and inclusive school education is an ongoing endeavour. It was the Right of Children to Free and Compulsory Education (RTE) Act 2009, followed by the Right of Persons with Disablities (RPWD) Act of 2016, that added much-needed impetus towards this obligation of ensuring equitable and inclusive education. However, a closer observation at the implementation level reveals loopholes that need to be addressed. The National Education Policy (NEP) 2020 renewed commitment has added the much-needed fillip towards addressing these hitherto existing lacunas in our education system. This article contends that despite a luminous and well-scripted policy documents, ensuring an inclusive and equitable education is still far-fetched without the active participation and collaboration amongst the primary stakeholders—parents, teachers, school heads, peers, etc. The current study based on secondary sources is the result of the analysis and argument drawn via literature reviews. The study establishes that a concerted effort by the stakeholders is critical to bridge the existing gaps in our education system pertaining to equitable and inclusive education. Furthermore, the cooperation and empathy of the stakeholders towards all sections of society will determine how many defects could be reduced or eliminated paving the way for achieving equitable and inclusive education.